An Early Islamic Kufic Inscription Inside an Open Air Mosque in the Faynan Area, Southern Jordan: An Archaeological and Textual Analysis (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
The present study examines an Islamic mosque that dates back to the early Islamic periods and that is constructed in the style of open, unroofed desert mosques (Open Air). The mosque is located in the Faynan region of southern Jordan, and it features an Islamic inscription that consists of seven lines written in Kufic script. This inscription was engraved on a stone  inside the mosque's mihrab. It bore part of the construction date, the first name of the mosque's builder or the writer of the inscription, and a request for mercy. The importance of this study lies in the fact that it provides a new addition to archaeological studies, especially the early Islamic period in the Faynan region; however, previous studies focused on ancient periods, they and did not sufficiently address the early Islamic period. This study addressed two main topics: the mosque and the inscription
Keywords: Islamic Architecture; Desert Mosques; Kufic Inscriptions; Faynan